Influencia de la Acción Citotóxica de la Corriente Eléctrica Directa en la Interacción del Hospedero con Células Cancerosas - Bergues Cabrales, L.; Camué Ciria, H.; Pérez Bruzón, R.; Hinojosa Aldana, R.; Montes De Oca González, L.; Brito Delgado, R. (Revista Mexicana de Ingenieria Biomedica)
The interaction between normal and tumoral cell populations, under the cytotoxic action of the direct electric current is discussed. Due to the fact that tumoral cells are more electrosensitive than normal cells to the cytotoxic action of the direct electric current, a linear term is included in the Lotka-Volterra model that characterized the inhibition or delay in tumoral cell growth, depending on the effectiveness of the therapeutic scheme. In addition, the bifurcations that this dynamical system suffers are described for the different situations obtained, which are associated to the situations that appear in Clinical Oncology.